PENGARUH SISTEM INFORMASI AKUNTANSI PENGGAJIAN TERHADAP EFEKTIVITAS PENGENDALIAN INTERNAL (STUDI PADA HOTEL DI KABUPATEN LOMBOK TENGAH) - Rahdien Badu Alam; Animah Animah; Nurabiah Nurabiah (JURNAL AKUNTANSI, 2022)
This study aims to examine whether the payroll accounting information system has an effect on hotel internal control in Central Lombok Regency. The approach used is quantitative data. The population in this study were all hotels in Central Lombok Regency as many as 88 based on data on the website of the Central Statistics Agency of West Nusa Tenggara Province in 2021 (https://ntb.bps.go.id/), with the sample criteria being employees who carry out functions in the accounting or finance department and HR at the hotel. The sampling technique used is a saturated sample with a sampling result of 103 respondents. The collected data is processed using the smartPLS version 4.0 software. The results of this study indicate that the payroll accounting information system has a positive effect on the effectiveness of hotel internal controls in Central Lombok Regency. The results of this study support the Theory of Reasoned Action (TRA) theory which explains that a person or individual will realize that an accounting information system will produce benefits for the user.